Pengaruh Tunneling Incentive dan Mekanisme Bonus Terhadap Harga Transfer Dengan Tax Minimization Sebagai Variabel Moderasi - eka hariyani; Sri Ayem (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2021)
This study aims to examine the effect of tunneling incentives and bonus mechanisms on transfer prices with tax minimization as a moderating variable. The sample used in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2019 period, with the purposive sampling method obtained 22 companies. The data in this study were processed using the help of Statistical Packge for Socia Science (SPSS) with logistic regression and interaction moderation test. The hypothesis testing method uses a significance level of 5%. The results showed that incentive tunneling had a positive effect on transfer prices. The bonus mechanism has a negative and insignificant effect on transfer prices. Tax minimization cannot moderate the relationship between tunneling incentives and transfer prices. Tax minimization cannot moderate the relationship between the bonus mechanism and the transfer price.